Three new species of Goniagnathus (Hemiptera: Cicadellidae) from the Indian subcontinent with description of a new subgenus - Viraktamath, C.A.; Gnaneswaran, R. (Zootaxa, 2009)
Tropicognathus subgen. nov. of Goniagnathus is described with Goniagnathus fumosus Distant as the type species. Three new species, Goniagnathus (Tropicognathus) anufrievi sp. nov. (India: Karnataka), Goniagnathus (Tropicognathus) nepalicus sp. nov. (Nepal: Kathmandu) and Goniagnathus (Tropicognathus) zeylanicus sp. nov. (Sri Lanka) are described and illustrated. G. bicolor Distant is placed as a junior synyonym of G. fumosus Distant. A key to the subgenera and species of Goniagnathus from the Indian subcontinent is also given.
Keywords: Homoptera; Morphology; Classification; key; Distribution